Enhanced Photocatalytic Properties by Forming Tetragonal ZnX/PbO (X = S, Se) Hetero‐Bilayers: A Computational Prediction. Issue 8 (26th June 2018) - Zhou, Jia; Zhen, Xiaofeng
Abstract: The formation of van der Waals hetero‐layered structure is a promising strategy to improve the performance of 2D materials in energy‐related applications that is superior to the individual components. In the current theoretical work, first‐principles calculations are employed to investigate novel tetragonal (t‐) ZnX/PbO (X = S, Se) hetero‐bilayers (BLs). The state‐of‐the‐art computations based on quasiparticle GW and Bethe–Salpeter equation have been used to calculate the electronic and optical properties of t‐ZnX/PbO BLs. It is found that the t‐ZnX/PbO BLs have a strong optical absorption in the solar spectrum, making them potentially good candidates for solar energy harvesting. In addition, first‐principles calculations also show there is a clear charge transfer from ZnX layer to PbO layer. Abstract : First‐principles calculations, as well as state‐of‐the‐art computations based on quasiparticle GW and Bethe−Salpeter equation, were used to investigate the electronic and optical properties of novel tetragonal ZnX/PbO hetero‐bilayers. It is found that the tetragonal ZnX/PbO hetero‐bilayers have a strong optical absorption in the solar spectrum, making them potentially good candidates for solar energy harvesting.